Immune response profiling of HERV-W envelope proteins in multiple sclerosis: potential biomarkers for disease progression - Ruberto, Stefano; Domınguez-Mozo, María I.; Garcıa-Martınez, M. Angel; Cossu, Davide; Sechi, Leonardo A.; Alvarez-Lafuente, Roberto (Frontiers in Immunology, 2025)
IntroductionThe envelope proteins syncytin-1 and pHERV-W from the Human Endogenous Retroviral family ‘W’ (HERV-W) have been identified as potential risk factors in multiple sclerosis (MS). This study aims to evaluate both humoral and cell-mediated immune response to antigenic peptides derived from these proteins across different clinical forms and inflammatory phases of MS.MethodsIndirect enzyme-linked immunosorbent assay (ELISA) was employed to measure immunoglobulin G (IgG) responses to syncytin-1env 486-500 and pHERV-Wenv 486-504 peptides in MS patients. Discriminant analysis was used to assess whether clinical course prediction could be enhanced by integrating clinical variables with humoral response data against other MS-associated viral factors. Additionally, peripheral blood mononuclear cells from MS patients and healthy controls (HC) were analyzed for inflammatory responses following stimulation with these peptides.ResultsMS patients exhibited significantly elevated antibody titers against -pHERV-Wenv 486-504 and syncytin-1env 486-500 compared to HCs, with the highest levels observed in progressive MS forms. Discriminant analysis accurately predicted the clinical course in 75.3% of the cases, with an 85% accuracy rate for progressive MS. In vitro, stimulation with pHERV-Wenv 486-504 led to a notable increase in pro-inflammatory cytokine production by CD4, CD8, and CD19 cells compared to syncytin-1env 486-500. A strong correlation was found between pHERV- Wenv 486-504 induced cytokine production and EBV and CMV titers in MS patients.DiscussionThese findings suggest that the pHERV-W envelope protein could be a valuable biomarker for monitoring peripheral inflammation in MS.